2022
DOI: 10.3389/fnins.2022.1054948
|View full text |Cite
|
Sign up to set email alerts
|

A transformer-based generative adversarial network for brain tumor segmentation

Abstract: Brain tumor segmentation remains a challenge in medical image segmentation tasks. With the application of transformer in various computer vision tasks, transformer blocks show the capability of learning long-distance dependency in global space, which is complementary to CNNs. In this paper, we proposed a novel transformer-based generative adversarial network to automatically segment brain tumors with multi-modalities MRI. Our architecture consists of a generator and a discriminator, which is trained in min–max… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…This framework integrated a generator utilizing a 3D CNN-based encoder and decoder architecture, alongside a Resnet module and transformer block. Incorporating deep supervision and hierarchical feature analysis, this method showcased superior generalization for brain tumor segmentation compared to other approaches [9].…”
Section: Literature Reviewmentioning
confidence: 98%
“…This framework integrated a generator utilizing a 3D CNN-based encoder and decoder architecture, alongside a Resnet module and transformer block. Incorporating deep supervision and hierarchical feature analysis, this method showcased superior generalization for brain tumor segmentation compared to other approaches [9].…”
Section: Literature Reviewmentioning
confidence: 98%
“…Transformer-based methods for glioma included. [49][50][51][52]55,57,59 Jiang et al 59 proposed a SwinBTS to introduce the SwinTransformer to a U-shape structure to fulfill the task of 3D brain tumor…”
Section: Brain Tumor Segmentationmentioning
confidence: 99%
“…Accounting for 80% of malignant brain tumors, glioma is difficult to automatically diagnosed due to its changeable appearance and ambiguous boundary. Transformer‐based methods for glioma included 49–52,55,57,59 . Jiang et al 59 proposed a SwinBTS to introduce the SwinTransformer to a U‐shape structure to fulfill the task of 3D brain tumor segmentation.…”
Section: Medical Image Segmentationmentioning
confidence: 99%
“…The Transformer structure is proposed based only on the self-attention mechanism, completely eliminating the convolutional structure, and is powerful in modeling global context is powerful, and several studies have shown that Transformer-based frameworks also achieve state-of-the-art performance on a variety of computer vision tasks ( 21 ). However, the self-attentiveness in Transformer requires large computation and memory consumption when dealing with long sequences, and the sparse nature of medical image data makes the model prone to overfitting during the training session, which hinders the application of Transformer in medical image segmentation tasks, which has been tried and tested in the field of natural image processing ( 22 , 23 ). To reduce the number of computational parameters, we refer to the approach in Swin Transformer, which uses two layers of attention structures with a hierarchical design, including a non-overlapping local window, and an overlapping cross-window ( 18 ).…”
Section: Introductionmentioning
confidence: 99%